Different Antiferromagnetic Coupling between 5, 5′‐ and 10, 10′‐Linked Iron(III) Corrole Dimers. Issue 10 (15th March 2017) - Tanaka, Takayuki; Ooi, Shota; Ide, Yuki; Ikeue, Takahisa; Suzuki, Masaaki; Chen, Peter P.‐Y.; Takahashi, Masashi; Osuka, Atsuhiro
Abstract : Two Fe III corroles were connected through a single meso–meso linkage at different positions, that is, 5, 5′‐linkage and 10, 10′‐linkage, which led to the observations of position‐dependent antiferromagnetic interactions between the two iron(III) corrole units. The iron(III) centers were found to exhibit an intermediate‐spin state, S = 3/2, under ambient conditions on the basis of 1 H NMR spectra, Curie plots, Mössbauer spectroscopy, and super‐conducting quantum interference device (SQUID) measurements. In previous reports, the X‐ray structure of dipyridine tris(pentafluorophenyl)corrolato iron(III) was assigned as a six‐coordinate species, but the 10, 10′‐linked and 5, 5′‐linked dimers preferred five‐coordinate geometry in the solid state. In addition, a mixed five‐coordinate/six‐coordinate dimer was also obtained, implying a susceptibility of the coordination mode to the crystal packing force. By summarizing the results, it can be concluded that pyridinate–iron(III) tris(pentafluorophenyl)corroles can be better described as five‐coordinate, intermediate‐spin ( S = 3/2) species under ambient conditions in toluene, whereas a dominant contribution of six‐coordinate low‐spin ( S = 1/2) iron(III) complex appears when coordinated with stronger axial ligands such as imidazole at low temperature. Complementary to these interpretations, the 10, 10′‐linked dimer exhibited a larger antiferromagnetic interaction between the two iron(III) corroles ( J = –2.04 cm –1 ) than that of the 5, 5′‐dimer ( J = –0.64 cm –1 ). Abstract : Different magnetic behaviors were observed in iron(III) complexes of 5, 5′‐ and 10, 10′‐linked corrole dimers. The axial ligand coordination mode is sensitive between the five‐coordinate intermediate‐spin ( S = 3/2) state and six‐coordinate low‐spin ( S = 1/2) state. Accordingly, the pyridinate–iron(III) corroles is better described as five‐coordinate, intermediate‐spin species under ambient conditions.